Report of the Study Team on Tribal Development Programmes All-India - Planning Commission, Government of India (Planning Commission, Government of India, 1969)
At the instance of the Planning Commission, the Committee on Plan Projects constituted in its Resolution No. COPP/ADM/16(l)/66, dated 26th October, 1966, (Annexure I) a Study Team on Tribal Development Programmes with the object of giving practical effect to the recommendations made in the Original Fourth Five Year Plan Draft Outline for the welfare of Scheduled Tribes and for assisting State Governments in evolving concrete schemes of development specially adapted to the needs and conditions of tribal communities and areas. The Team was required to (a) study the problems and needs of the tribal communities in each State; (b) appraise the working of tribal development programmes, specially during the Third Five Year Plan; (c) ascertain how far the schemes formulated so far have enabled the tribal communities to secure an adequate share in the benefits accruing from the general development programmes; (d) make detailed recommendations regarding the lines on which the schemes should be oriented in the Fourth Plan to accelerate progress; and (e) suggest measures for strengthening the administrative machinery and harnessing tribal leadership and institutions so as to ensure their fullest participation in the tasks of economic and social development.
Committee on Plan Projects
Planning Commission
Keywords: Tribal Development; Community Development of Tribal Areas; Tribal development programmes